2019
DOI: 10.35790/jkp.v7i1.24353
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Tingkat Kepuasan Pasien BPJS Dan Non BPJS Terhadap Pelayanan Pendaftaran Di Rsud Tobelo

Abstract: Abstrack :Patient satisfaction level is considered as one of the very important dimension and is oneof the main indicators of the standard of a health facility which is due to the influence of health careon the hospital and it is this which makes the measurement of patient satisfaction is an importantcomponent.The purpose of this study was to determine the differences between patient satisfactionlevel on BPJS and Non BPJS users over registration services in Tobelo hospitals. This researchmethod using cross sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
0
2
1
5
Order By: Relevance
“…While 10 Non BPJS patients, 8 of them felt optimal service and 2 of them were quite satisfied with the existing services. (Ozzi et al, 2016). The results of this study are different from the results of Ningtyas' research (2019), where the results of this study found that BPJS patients were satisfied with the registration service compared to non-BPJS patients.…”
Section: Introductioncontrasting
confidence: 99%
“…While 10 Non BPJS patients, 8 of them felt optimal service and 2 of them were quite satisfied with the existing services. (Ozzi et al, 2016). The results of this study are different from the results of Ningtyas' research (2019), where the results of this study found that BPJS patients were satisfied with the registration service compared to non-BPJS patients.…”
Section: Introductioncontrasting
confidence: 99%
“…Tingkat kepuasan pasien dianggap sebagai salah satu dimensi yang sangat penting, berkualitas dan merupakan salah satu indikator utama dari standar suatu fasilitas kesehatan yang merupakan akibat pengaruh pelayanan kesehatan atas pihak rumah sakit. Hal inilah yang membuat pengukuran kepuasan pasien menjadi komponen penting (Bitjoli & Buanasari, 2019). Mutu pelayanan yang baik tidak hanya diukur dari kemewahan fasilitas, kelengkapan teknologi dan penampilan fisik akan tetapi dari sikap dan perilaku karyawan harus mencerminkan profesionalisme dan mempunyai komitmen tinggi.…”
Section: Pendahuluanunclassified
“…Setiap orang memiliki hak yang sama terhadap pelayanan kesehatan, baik sebagai pasien baru maupun pasien kunjungan ulang ataupun pasien BPJS dan non BPJS. Penelitian sebelumnya menunjukkan terdapat perbedaan yang signifikan antara tingkat kepuasan pasien BPJS dan Non BPJS terhadap pelayanan pendaftaran di RSUD Tobelo (Bitjoli et al, 2019). Penelitian Yanuarti et al, (2021) menunjukkan ada perbedaan kepuasan antara pasien BPJS dan pasien umum.…”
Section: Pendahuluanunclassified
“…Sejalan dengan 2021. Jurnal Kesmas Asclepius 3 (2) 49-59 penelitian sebelumnya tentang kepuasan pelayanan yang menemukan bahwa pasien BPJS dan Pasien Non BPJS paling banyak pada kelompok umur 31-40 tahun (Bitjoli et al, 2019). Berbeda dengan penelitian yang dilakukan oleh Arnaya & Niryana (2020) menemukan kelompok umur terbanyak adalah 35-44 tahun (33,3%).…”
Section: Pembahasanunclassified